Smart Helmet with Onboard Camera - Vimal Kumar M N, Aakash Ram S, Rubesh C M, Sikkandar Batcha M (International Journal of Control and Automation, 2020)
Nowadays most of the countries are enforcing their citizen to wear helmet while riding bike and not  to ride bike when the person is under the influence of alcohol. Road safety among motorcyclists becomes a major issue of concern because of violating the rules. In order to overcome this problem, Smart Helmet with On board Camera is developed. The system includes an alcohol sensor to detect whether the rider has consumed alcohol and a helmet sensing switch to detect whether the rider is wearing helmet.  The entire  setup is placed inside the helmet. Rider can turn ON the engine only if he wears the helmet without the consumption of alcohol and this system enables detection of an accident by using camera  and  force resistive sensor at any place and intimates about the accident and location to predefined numbers  using  GSM and GPS module. MQ-3 Alcohol sensor is used for the detection of alcoholic breath of the rider which is interfaced with Raspberry pi by the use of analog to digital converter MCP3008 and Logic level converter. A camera is also placed on the helmet to detect the signboards and to assist the drivers by detecting the traffic sign.